Effects of cortical anodal transcranial direct current stimulation on swallowing biomechanics. Issue 11 (13th August 2018) - Doeltgen, Sebastian H.; Rigney, Lakkari; Cock, Charles; Omari, Taher
Abstract: Background: Anodal transcranial direct current stimulation (tDCS) has demonstrated effects on corticobulbar excitability and swallowing function as assessed via clinical rating scales in stroke cohorts. Biomechanical effects of anodal tDCS on swallowing remain largely unexplored. We investigated how anodal tDCS applied over the floor of mouth (FOM) representation on the primary motor cortex affects swallowing biomechanics in healthy participants. Methods: Anodal and sham tDCS were applied for 20 minutes at 1.5 mA. Corticobulbar excitability was assessed using motor evoked potentials at baseline and 0, 15, 30 and 45 minutes post‐tDCS, as assessed by transcranial magnetic stimulation. Swallowing function was assessed pre‐ and post‐tDCS using routine clinical assessments (Study 1) and pharyngeal high resolution impedance manometry (Study 2). Key Results: Study 1 ( n = 17) showed increased corticobulbar excitability and performance on a skilled swallowing task following anodal wetDCS, but not sham tDCS. In Study 2 ( n = 10) anodal tDCS resulted in increased bolus admittance across the upper esophageal sphincter, but decreased pharyngeal and upper esophageal contractile vigor. Conclusions: Clinical improvements of dietary intake are likely driven by swallowing neuroplastic reorganization which improves bolus admittance across the upper esophageal sphincter (UES). Inferences: The documented changes make motor cortical application of anodal tDCS a promising adjunct to swallowing rehabilitation practice. Abstract : A one‐off session of anodal transcranial direct current stimulation increased the excitability of cortical motor projections to the swallowing musculature, resulting in subtle changes in swallowing biomechanics in healthy volunteers. The observed changes may be of clinical relevance for individuals with impaired swallowing.